2022
DOI: 10.12688/gatesopenres.13600.1
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring sufficient service capacity for removals of long-acting reversible contraceptives: a mixed-method study of provider experiences in Senegal

Abstract: Background: As the number of implants and intrauterine devices (IUD) used in sub-Saharan Africa continues to grow, ensuring sufficient service capacity for removals is critical. This study describes public sector providers’ experiences with implant and IUD removals in two districts of Senegal. Methods: We conducted a cross-sectional study with providers trained to insert implants and IUDs from all public facilities offering long-acting reversible contraceptives. Data collection elements included a survey with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…All facilities had staff trained on both insertion and removal. We observed some minor gaps related to the availability of equipment and consumables for regular removals which aligns with findings from the provider interviews from this study reported elsewhere ( 16 ). Importantly, this study was performed in public facilities benefiting from NGO support, therefore as found in other studies, the availability of equipment and consumables may be high compared to other facilities ( 7 , 21 – 23 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All facilities had staff trained on both insertion and removal. We observed some minor gaps related to the availability of equipment and consumables for regular removals which aligns with findings from the provider interviews from this study reported elsewhere ( 16 ). Importantly, this study was performed in public facilities benefiting from NGO support, therefore as found in other studies, the availability of equipment and consumables may be high compared to other facilities ( 7 , 21 – 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…We conducted a cross-sectional survey of all public health facilities offering insertion of long-acting reversible contraceptives (LARCs) in two districts of Senegal - urban Dakar Centre and primarily rural Kolda). This study was part of a larger project that also examined client and provider experiences with removal services; these results are presented elsewhere ( 16 , 17 ). Trained research assistants administered the health facility questionnaire to the in-charge of the facility or designee (maternal and child health department in-charge or midwife); after they provided written consent for the health facility, these respondents could solicit input from other staff based on expertise relevant to specific questions.…”
Section: Methodsmentioning
confidence: 99%
“…Training opportunities that foster clinical competency are needed for training in removals: Christofield et al reported that a substantial percentage of providers in Uganda and Kenya never practiced implant removal on a client during training (18). In Senegal, Lebetkin et al reported substantially higher percentages of providers who felt confident in performing uncomplicated removals (96 percent) than in our Nigeria assessment, but 15 percent did not feel confident removing non-palpable implants and an additional 15 percent did not provide this service (36).…”
Section: Strengthen Provider Competency and Confidence In Implant Rem...contrasting
confidence: 64%
“…Despite this increase, there has been little attention to LARC removal in LMICs, prompting researchers and advocates to identify LARC removals as an overlooked aspect of contraceptive care, with training and availability of services for removals lagging behind insertions [6]. The limited existing literature on LARC removals from LMICs points to barriers including long wait times, associated costs, provider refusal and unavailability, and provider training [2,[7][8][9][10][11][12]. Providers can act as gatekeepers to LARC removal, encouraging clients to continue use of the method or refusing to provide the service altogether, reflecting what has also been documented in the U.S. [12][13][14].…”
Section: Introductionmentioning
confidence: 99%